Families in motion. The case of Romanian women in Spain - Navaz, Liliana Suárez; Bordonaba, Paloma Crespo (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2025)
The gender variable croses clearly the romanian migratory process. The women’s role inside of the family, hided by the patriarchal ideology which keeps her as main guarantee of the transmission of its own ideology, is shown in the migratory processes. After a first theoretical part about the construction of the family concept and a mythic familiar model, we will see the place that the family has in the migratory process and how the family can become a unit of analysis in these processes. The last part of the paper analyzes the different migratory projects according to the implication of the family in them, with special attention to the role of women.